2003
DOI: 10.1021/ol035184b
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic Ligand-Free Palladium as a Catalyst in the Heck Reaction. A Comparison with a Palladacycle

Abstract: [reaction: see text] Ligand-free Pd(OAc)(2) can be used as a catalyst in the Heck reaction of aryl bromides as long as the amount of catalyst is kept between 0.01 and 0.1 mol %. At higher concentrations palladium black forms and the reaction stops. The actual catalyst is monomeric. Palladacycles merely serve as a source of ligand-free palladium in Heck reactions of aryl bromides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
282
5
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 557 publications
(315 citation statements)
references
References 52 publications
19
282
5
7
Order By: Relevance
“…Thus, the higher the S C -1 ratio the higher the turnover frequency will be. 147 Both Cu(0) as well as Cu(I) and Cu(II) oxide can form nanoparticles. Moreover, as in most reactions halide anions, either from the substrate or from the used copper salt precursor, are abundant, even under apparently homogeneous reaction conditions, the presence of nano-particles of copper halide salts (copper in various oxidation states with bridging halides, cf.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the higher the S C -1 ratio the higher the turnover frequency will be. 147 Both Cu(0) as well as Cu(I) and Cu(II) oxide can form nanoparticles. Moreover, as in most reactions halide anions, either from the substrate or from the used copper salt precursor, are abundant, even under apparently homogeneous reaction conditions, the presence of nano-particles of copper halide salts (copper in various oxidation states with bridging halides, cf.…”
Section: Discussionmentioning
confidence: 99%
“…using extremely low palladium acetate catalyst loadings, which they dubbed "homeopathic" ligand free palladium catalysts [29][30][31]. They reported that the Suzuki reaction of aryl bromides were catalysed in high yields using 0.02-0.05 mol% palladium and even the reactions of some aryl chlorides were catalysed using 0.005- However, further TEM analysis of the recycled MWCNT/Pd-DMAP NP composite shows a further aspect of interest within this reaction mixture.…”
Section: Interestingly De Vries Et Al Have Identified the Catalysis mentioning
confidence: 99%
“…Therefore, further work continued using the alternative route where the Heck reaction was involved in the initial step. Firstly, Heck reactions between 3-bromobenzaldehyde (12) and commercially available styrenes (23-27) were performed in Nmethylpyrrolidone containing palladium (II) acetate (0.06% mole) as catalyst and anhydrous sodium acetate as base [22]. Except for the reactant 4-aminostyrene 27, all styrenes (23-26) gave corresponding stilbenes (35-38) in good yields (Table 4).…”
Section: Resultsmentioning
confidence: 99%